The Department of Justice as a gatekeeper in whistleblower-initiated corporate fraud enforcement: Drivers and consequences - Heese, Jonas; Krishnan, Ranjani; Ramasubramanian, Hari (Journal of Accounting and Economics, 2021)
We examine drivers and consequences of U.S. Department of Justice (DOJ) oversight of whistleblower cases of corporate fraud against the government. We find that the DOJ is more likely to intervene in and conduct longer investigations of cases that have a higher chance of victory and yield greater monetary proceeds, indicating that DOJ enforcement is influenced by its performance measures. DOJ intervention also affects the firm- and aggregate-level fraud environment. Firms subject to DOJ intervention improve their employee relations, internal controls, and board independence, and experience lower future whistleblowing risk. Whistleblowers avoid courts and agencies with low DOJ intervention rates. In contrast, we do not find that cases pursued by whistleblowers alone affect firms' or whistleblowers' behavior, suggesting that public enforcement through DOJ intervention has a greater deterrent effect on fraud than private enforcement by whistleblowers acting alone.